Direct laser writing of μ-chips based on hybrid C–Au–Ag nanoparticles for express analysis of hazardous and biological substances1. Issue 7 (7th April 2015) - Bashouti, M. Y.; Manshina, A.; Povolotckaia, A.; Povolotskiy, A.; Kireev, A.; Petrov, Y.; Mačković, M.; Spiecker, E.; Koshevoy, I.; Tunik, S.; Christiansen, S.
<x xml:space="preserve">Abstract</x> μ-Chips based on metal nanoparticles embedded in amorphous carbon matrix were realized by laser writing. The μ-chips can detect small fractions of bio-agents & hazardous compound.